THE ROLE OF THE FAMILY ENVIRONMENT IN CHILD DEVELOPMENT AT AL IZZAH KINDEGARTEN, PURI DISTRICT, MOJOKERTO REGENCY - Lida Khalimatus Sadiyah; Tria Wahyuningrum (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2026)
The kindergarten years represent the